Improving the communication performance in synchronous collaborative application - Maganlal, Jayesh M. Patel (2005)
Point to point communication models and protocols such as TCP, were designed merely for the use in client-server applications. As the demand for collaborative applications increases, communication involving multi point and proper network bandwidth utilization arises as an issue. The main purpose of this research was to investigate the communication layer in synchronous collaborative systems and introduce an alternative communication model to improve the performance of the system in the context of bandwidth utilization. Reliable multicasting is implemented to provide reliable communication between multicast groups and clients within those groups. Multicasting enables multiparty communication across a wide area to sparsely distributed groups by minimizing the network load but the issue of reliability remains a problem. This research focused on the reliable multicast service that is provided by Spread, in order to handle the bandwidth more efficiently, to provide reliable service and to meet future requirements. This research also looked into alternative means of communication by implementing collaboration on wired and wireless networking. Results obtained from the performance experiment contribute towards improving the performance of communication in synchronous collaborative environment